Host genomics and control of tuberculosis infection (2013)
ABSTRACT: Tuberculosis (TB), caused by the human pathogenic bacterium Mycobacterium tuberculosis, poses a major global health problem. The tubercle bacillus is transmitted from person to person by aerosol, but only a proportion of those in contact with infectious aerosol particles will become infected. If infection occurs, less than 10% of those infected will develop clinical signs of TB, while the majority will develop latent TB infection (LTBI). The identification and treatment of LTBI persons is a major aspect of TB control, especially in low-incidence, highly developed nations. In the absence of a gold standard test for latent TB, infection is inferred with the help of either the in vivo tuberculin skin test or in vitro interferon gamma release assays of anti-mycobacterial immunity. Recent work has observed high heritability of these immune assays indicating the critical role of the host genetic background on the establishment of infection and latency. Additional genetic studies have identified the host genetic background as an important covariate for the proper interpretation of the results obtained from LTBI assays. Taken together, these data suggest TB surveillance and control can likely be improved by including host genetic information into the interpretation of these widely used assays.